Gerakan Transnasional Ikhwanul Muslimin di Mesir dan Palestina - Azis, Abdul Azis (State Islamic Institute of Kudus (IAIN Kudus), 2019)
The Transnational Movement of Muslim Brotherhood in Egypt and Palestine.The Muslim Brotherhood is a large transnational movement in the Middle East. Its influence is very strong in education, then extends to the fields of politics, economics, and culture. This research will map the position of the Muslim Brotherhood in Egypt, trace geneology, and the concept of movement. In addition, it also analyzes the influence of the Muslim Brotherhood in Egypt and its influence on the social and political changes of Palestine. This will be explained using a descriptive analysis approach. This study concluded that the policies of the ruling leaders in Egypt experienced changes and ups and downs, especially in pre and post-revolution. This is related to its interaction with the Muslim Brotherhood. The struggle of the Muslim Brotherhood with the Egyptian government is often colored by conspiracies, oppression, which are then greeted with demonstrations and competition for power.